Hubungan Psikologi Sosial Dalam Perilaku Manusia - Yenti Arsini; Ferren Audy Febina Sitompul; Kartina Anggreini Nasution (Politeknik Kampar, 2023)
Several threats continue to cause species declines and even extinctions, despite increased efforts from non-governmental organizations, academics, and governments over the past few decades. Conservation scientists must be interested in the factors that motivate human behavior because resource use by a growing human population is a significant driver of biodiversity loss. Monetary models have been applied to human decision making for a long time; in any case, people are not ?nancially sane creatures and different qualities of the chief (counting demeanor) and the tension that individuals see to act with a particular goal in mind (emotional standards) may in?uence navigation; Social psychologists who are interested in human decision-making take these characteristics into consideration. We look at how behavioral theories from social psychology have been applied to conservation and resource management. Since many studies focus on general attitudes toward conservation rather than specific conservation-relevant behaviors, they are of limited use when developing interventions to change specific behaviors (such as reducing hunting of endangered species). Behaviors that have an impact on conservation goals will be better understood, allowing for improved intervention design by more specifically defining the behavior of interest and investigating attitude in the context of other social-psychological predictors of behavior (such as subjective norms, the presence of facilitating factors, and moral obligation).